Rigidity-toughness balanced polylactic acid composite material and preparation method thereof

By introducing Pebax-GMA and SiO2 into PLA composite materials, the core-shell structure is formed, which solves the problem of unbalanced rigidity and toughness of PLA composite materials, and achieves excellent rigidity and toughness balance performance and biodegradability of the material.

CN119613937APending Publication Date: 2025-03-14CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510161604.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The rigidity and toughness of existing PLA composites are not balanced, resulting in problems of brittleness or insufficient rigidity in some applications.

Method used

By blending biodegradable Pebax-GMA and inorganic rigid particle SiO2 with PLA, a core-shell structure with SiO2 as the core and Pebax-GMA as the shell is formed, thereby improving the rigid and tough equilibrium performance of the material.

Benefits of technology

The excellent rigid and tough balance performance of PLA composites is achieved, the notch impact strength can reach 24 times that of pure PLA, and the bending modulus can still retain 73% of pure PLA and maintain the biodegradability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613937A_ABST
    Figure CN119613937A_ABST
Patent Text Reader

Abstract

The invention discloses a polylactic acid composite material with balanced rigidity and toughness and a preparation method thereof, relates to the technical field of polymer composite materials, and solves the problem that the rigidity and toughness of a polylactic acid composite material in the prior art cannot maintain balance. The preparation method comprises the following steps: drying polylactic acid (PLA), a glycidyl methacrylate grafted polyether amide copolymer (Pebax-GMA) and silicon dioxide (SiO2) in a drying oven, weighing the dried PLA, Pebax-GMA and SiO2 in proportion, and carrying out melt blending in an internal mixer to obtain the polylactic acid composite material. According to the invention, PLA is taken as a polymer matrix, SiO2 is taken as a core, Pebax-GMA is taken as a shell, and the shell is wrapped outside the core to form a core-shell structure, so that rigid-tough balance and biodegradable material design of the PLA composite material are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, and in particular to a polylactic acid composite material with balanced rigidity and toughness and a preparation method thereof. Background Art

[0002] Polylactic acid (PLA) is a renewable plastic with good biocompatibility and biodegradability, which is widely used in packaging, medical, textile and agriculture. The inherent brittleness, low elongation at break and low impact strength of PLA have become the main factors limiting its further application. At present, chemical modification and physical modification are usually used to improve the toughness of PLA. Chemical modification mainly improves the toughness of PLA by copolymerizing PLA with other polymers to prepare PLA copolymers. Although this method can effectively improve the mechanical properties of PLA, its process is relatively complicated and requires the use of high-cost raw materials and processing. In addition, chemical modification may affect the biodegradability and other physical properties of PLA. Physical modification improves the impact resistance and ductility of PLA by blending PLA with rubber or other elastomers. This physical modification method is simple, convenient and low-cost, and has become the most commonly used modification method in industrial production. However, physical modification still has problems in controlling the blending ratio and consistency of the properties of the modified material. For example, the balance between rigidity and toughness is still an important topic of current research.

[0003] Chinese patent document CN103788605A provides a PLA composite material and a preparation method thereof. The patent uses component A (PLA and polyetheramide copolymer grafted with glycidyl methacrylate) and component B (thermoplastic starch acetate and PLA grafted with maleic anhydride), and the components A and B are mixed in different proportions to prepare a highly impact-resistant, low-cost, fully biodegradable PLA composite material. The PLA composite material of the invention has good overall impact resistance, but its rigidity decreases too much.

[0004] Chinese patent document CN106916423A provides a high-toughness PLA composite material and a preparation method thereof. The patent improves the impact resistance of the composite material by grafting and modifying the elastomer and using the grafted modified elastomer to toughen PLA. The invention has a simple production process and effectively improves the toughness of PLA, but since the elastomers in the patent are all non-biodegradable materials, this will reduce the biodegradability of the PLA composite material, and the introduction of a large number of low-modulus elastomers will reduce the rigidity of the PLA composite material.

[0005] In summary, the development of a PLA composite material with a balance of rigidity and toughness and retaining biodegradability is of certain significance to the development of the field of polymer composite materials. Summary of the invention

[0006] In order to solve the problem that the rigidity and toughness of the PLA composite materials in the prior art cannot be balanced, the present invention proposes a PLA composite material with balanced rigidity and toughness and a preparation method thereof. The technical solution of the present invention is as follows: A PLA composite material with balanced rigidity and toughness is prepared from the following components by weight: 16 parts of PLA, 1-3 parts of polyetheramide copolymer grafted with glycidyl methacrylate (Pebax-GMA), and silicon dioxide (SiO 2 ) 1~3 portions; The SiO 2 Including hydrophobic SiO 2 and hydrophilic SiO 2 ; The preparation method of Pebax-GMA comprises the following steps: adding polyetheramide copolymer (Pebax) into an internal mixer for premixing, and then adding glycidyl methacrylate (GMA), vinyl-2-pyrrolidone (NVP) and diisopropylbenzene peroxide (DCP) for blending to prepare Pebax-GMA; Furthermore, the Pebax is a random copolymer prepared from polyethylene glycol (PEG) of a flexible segment and bio-based nylon 11 (PA11) of a rigid segment; Furthermore, the mass ratio of Pebax, GMA, NVP and DCP is 100:3~5:3~5:0.3~0.5; Further, the premixing time is 2 min; Further, the blending time is 3 to 5 min; Further, the blending temperature is 175-185°C; Furthermore, the blending speed is 40-80 rpm.

[0007] A method for preparing a PLA composite material with a balanced rigidity and toughness, comprising the following steps: PLA, Pebax-GMA and SiO 2 Place in an oven to dry, weigh the dried PLA, Pebax-GMA and SiO 2 Putting into an internal mixer for melt blending to obtain a PLA composite material; Furthermore, the drying time is 12 h; Further, the drying temperature is 50°C; Further, the melt blending temperature is 180°C; Further, the melt blending speed is 80 rpm; Furthermore, the melt blending time is 5 min.

[0008] Compared with the prior art, the present invention solves the problem that the rigidity and toughness of PLA composite materials cannot be balanced, and the specific beneficial effects are: 1. Excellent rigidity and toughness balance: The present invention combines biodegradable Pebax-GMA and inorganic rigid particles SiO 2 PLA composites were prepared by blending with PLA. The composites were composed of SiO 2 The PLA composite material has a core-shell structure with Pebax-GMA as the core and Pebax-GMA as the shell. As the thickness of the shell increases, the notched impact strength is greatly improved, which can be up to 24 times that of pure PLA, while its flexural modulus can still retain 73% of that of pure PLA. When the notched impact strength of the PLA composite material is 11 times that of pure PLA, the flexural modulus is 87% of that of pure PLA. It can be seen that the PLA composite material prepared by the present invention has excellent rigidity-toughness balance performance.

[0009] 2. Core-shell structure: The present invention utilizes SiO2 with high hardness, high chemical stability and good mechanical strength. 2 The core is made of SiO2 and Pebax-GMA, which has excellent flexibility, wear resistance and good biodegradability, is used as the shell. The shell is wrapped around the core to form a core-shell structure. 2 The core provides strength and rigidity, ensuring that the PLA composite material has good mechanical properties and compressive resistance; while the Pebax-GMA shell layer reduces the brittleness of the PLA composite material through its flexibility and stretchability, and improves the impact resistance of the material. At the same time, the epoxy groups in Pebax-GMA can react with the carboxyl and hydroxyl groups in PLA, effectively improving the compatibility of PLA and Pebax at the interface, which is more conducive to the formation of a core-shell structure. In addition, SiO 2 Smaller particle size and higher surface activity are conducive to the coating of shell materials, improving the stability of the core-shell structure and further enhancing the mechanical properties of the material.

[0010] 3. Biodegradability: The present invention retains the advantage of PLA being biodegradable, and introduces the biodegradable polymer Pebax-GMA on this basis, so that the PLA composite material has excellent biodegradability. 2 The introduction of does not affect the degradation degree of the PLA composite material, and the present invention realizes the rigidity-toughness balance and biodegradable material design at the same time. The present invention has a simple preparation process, does not produce harmful substances during the preparation process, is environmentally friendly, and meets the current requirements for the sustainable development of PLA composite materials.

[0011] 4. Thermal stability and chemical stability: SiO 2 It has good thermal stability and good resistance to most chemicals. In theory, adding SiO 2Compared with other materials with poor physical and chemical property stability, the core structure material can significantly improve the thermal stability and chemical stability of the material, and can better maintain its performance in application scenarios at high temperatures or requiring contact with chemical reagents. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a liquid nitrogen brittle fracture cross-section SEM image of the PLA composite material prepared in Example 2; Figure 2 This is a liquid nitrogen toughness fracture cross-section SEM image of the PLA composite material prepared in Example 3; Figure 3 These are photos of the brittle fracture of the PLA composite material prepared in Example 2 and the ductile fracture of the PLA composite material prepared in Example 3. DETAILED DESCRIPTION

[0013] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0014] Example 1. Pebax was added into an internal mixer and premixed for 2 min, and GMA, NVP and DCP were continuously added and blended at 180°C for 5 min with a blending speed of 80 rpm. The mass ratio of Pebax, GMA, NVP and DCP was 100:3:3:0.3, and Pebax-GMA was prepared.

[0015] Example 2. PLA, Pebax-GMA and hydrophobic SiO 2 The dried PLA, Pebax-GMA and hydrophobic SiO 2 The materials were put into an internal mixer for melt blending at a mass ratio of 8:1:1. The melt blending temperature was 180°C, the rotation speed was 80 rpm, and the melt blending time was 5 min to prepare a PLA composite material.

[0016] The PLA composite material prepared in Example 2 was etched with n-butanol at 80°C for 12 h to remove Pebax-GMA. Figure 1 This is a liquid nitrogen brittle fracture cross-section SEM image of the PLA composite material prepared in Example 2. Figure 1 Several holes can be found evenly distributed in the PLA matrix. This is because after the Pebax phase is etched, a large amount of SiO 2They aggregated together and were distributed in the middle of the interface between PLA and Pebax, and no core-shell structure was formed at this time.

[0017] Example 3. The difference between this embodiment and embodiment 2 is that the hydrophobic SiO 2 The particle size is 300 nm, and the rest of the preparation process and conditions are the same as those in Example 2.

[0018] The PLA composite material prepared in Example 3 was etched with n-butanol at 80°C for 12 h to remove Pebax-GMA. Figure 2 This is a liquid nitrogen toughness fracture cross-section SEM image of the PLA composite material prepared in Example 3. Figure 2 Some SiO 2 distributed in the pores, which indicates that SiO 2 The core-shell structure is composed of a core and a shell. Figure 3 Schematic diagram of the brittle fracture of the PLA composite material prepared in Example 2 and the tough fracture of the PLA composite material prepared in Example 3. Generally, when the notched impact strength of the PLA composite material reaches 30 kJ / m 2 When the fracture temperature is above 0.05, the fracture of PLA composite material is ductile fracture, otherwise it is brittle fracture; the surface of brittle fracture is smooth, while the surface of ductile fracture is rough and accompanied by stress whitening.

[0019] Example 4. The difference between this embodiment and embodiment 2 is that the hydrophobic SiO 2 The particle size is 500 nm, and the rest of the preparation process and conditions are the same as those in Example 2.

[0020] Example 5. The difference between this embodiment and embodiment 2 is that the hydrophobic SiO 2 The particle size is 800 nm, and the rest of the preparation process and conditions are the same as those in Example 2.

[0021] According to the national standard GB / T1843-2008, the notched impact strength test of the PLA composite material prepared in Example 2-5 was carried out, and the cantilever beam test was carried out using an impact tester (XJUD-5.5) produced by Chengde Jinhe Instrument Manufacturing Co., Ltd., and the test temperature was 23±2°C. According to the national standard GB / T9341-2008, the flexural modulus test of the PLA composite material prepared in Example 2-5 was carried out using a universal testing machine (Instron-1121, UK), the bending rate was 2 mm / min, and the test temperature was 23±2°C. According to GB / T 1040.1-2006, the tensile test was carried out using a universal testing machine (Instron-1121, UK), the tensile rate was 10 mm / min, and the test temperature was 23±2°C.

[0022] Table 1 shows the mechanical properties test results of the PLA composite materials and pure PLA prepared in Examples 2-5. According to Table 1, it can be seen that the notched impact strength of the PLA composite material prepared in Example 2 is 15.0 kJ / m 2 The notched impact strength of the PLA composite materials prepared in Examples 3-5 is greater than 30 kJ / m 2 Among them, the notched impact strength of the PLA composite material prepared in Example 3 is 10 times that of pure PLA, and its flexural modulus is still 82% of that of pure PLA, showing excellent rigidity-toughness balance performance; the notched impact strength of the PLA composite material prepared in Example 4 is 19 times that of pure PLA, reaching the standard of super-tough PLA composite material (notched impact strength greater than 50 kJ / m 2 ), its flexural modulus is still maintained at 73% of pure PLA. Even though the flexural modulus retention effect is slightly lower than that of Example 3, it still has a good rigidity-toughness balance performance; the results of Example 5 are similar to those of Example 3.

[0023] Table 1

[0024] Example 6. The difference between this embodiment and embodiment 3 is that PLA, Pebax-GMA and SiO 2 The mass ratio of is 16:3:1, and the rest of the preparation process and conditions are the same as those in Example 3.

[0025] As shown in Table 2, the notched impact strength of the PLA composite material prepared in Example 6 is 72.7 kJ / m 2 , reaching 24 times that of pure PLA. Compared with the PLA composite material prepared in Example 3, the notched impact strength has been greatly improved. This is due to the SiO 2The increase in the content of core material leads to a significant increase in the thickness of the shell, which in turn greatly improves the notched impact strength, while its flexural modulus can still retain 73% of that of pure PLA.

[0026] Example 7. The difference between this embodiment and embodiment 6 is that hydrophilic SiO 2 The PLA composite material was prepared, and the rest of the preparation processes and conditions were the same as those in Example 6.

[0027] As shown in Table 2, the notched impact strength of the PLA composite material prepared in Example 7 is 68.3 kJ / m 2 , the notched impact strength of the PLA composite material prepared in Example 6 is slightly lower than that in Example 6. This is because PLA itself is hydrophilic and hydrophobic SiO 2 The particles repel each other and are more likely to exist in the elastomer Pebax-GMA, while the hydrophilic SiO 2 Particles are more likely to exist in the PLA matrix, and it also proves that SiO 2 The hydrophilicity and hydrophobicity of the particles have little effect on the rigidity-toughness balance of PLA composites.

[0028] Example 8. The difference between this embodiment and embodiment 6 is that the preparation process is carried out step by step. First, Pebax-GMA and SiO2 with a mass ratio of 3:1 are weighed. 2 , blending for 5 min at 190° C. and 80 rpm in an internal mixer to prepare component A; then weighing PLA and component A in a mass ratio of 4:1 for blending, and the rest of the preparation process is the same as that in Example 6 to obtain the PLA composite material of this example.

[0029] The notched impact strength of the PLA composite material prepared in Example 8 is 53.6 kJ / m 2 , which is lower than that in Example 6. Therefore, when preparing a PLA composite material with a balance of rigidity and toughness, the preferred method is to combine PLA, Pebax-GMA and SiO 2 The particles are prepared by blending together.

[0030] Example 9. The difference between this embodiment and embodiment 4 is that PLA, Pebax-GMA and SiO 2 The mass ratio of is 16:3:1, and the rest of the preparation process and conditions are the same as those in Example 4.

[0031] It can be seen from Table 2 that the notched impact strength of the PLA composite material prepared in Example 9 is 23.5 times that of pure PLA, and the flexural modulus is 71% of that of pure PLA. The notched impact strength is greatly increased compared with that in Example 4, while the flexural modulus changes slightly.

[0032] Example 10. The difference between this embodiment and embodiment 4 is that PLA, Pebax-GMA and SiO 2 The mass ratio of is 16:1:3, and the rest of the preparation process and conditions are the same as those in Example 4.

[0033] It can be seen from Table 2 that the notched impact strength of the PLA composite material prepared in Example 10 is 11 times that of pure PLA, and the flexural modulus is 87% of that of pure PLA.

[0034] Comparative Example 1. The difference between this comparative example and Example 5 is that this example does not add SiO 2 , the mass ratio of PLA to Pebax-GMA is 4:1, and the rest of the preparation processes and conditions are the same as those in Example 5.

[0035] According to Table 2, the notched impact strength of Comparative Example 1 is 14 times that of pure PLA, but the flexural modulus is only 69% of that of pure PLA, and the rigidity-toughness balance effect is not good.

[0036] Comparative Example 2. The difference between this comparative example and Example 5 is that Pebax-GMA, PLA and SiO are not added in this example. 2 The mass ratio of is 9:1, and the rest of the preparation process and conditions are the same as those in Example 5.

[0037] According to Table 2, the notched impact strength of Comparative Example 2 is almost the same as that of pure PLA, the flexural modulus is slightly improved compared with that of pure PLA, and the rigidity-toughness balance effect is not good.

[0038] Comparative Example 3. The difference between this embodiment and embodiment 10 is that the elastomer used is Pebax without GMA grafted thereto, and the rest of the preparation processes and conditions are the same as those of embodiment 10.

[0039] According to Table 2, the notched impact strength of Comparative Example 3 is only 13.8 kJ / m 2 , indicating that the prepared PLA composite material is brittle fracture, which is because the comparative example 3 is not grafted with GMA, and the reaction between Pebax and PLA produces a large number of dispersed phase particles, which is not conducive to toughening PLA, and the toughness decreases. However, the epoxy groups in GMA in Example 10 can react with the carboxyl and hydroxyl groups in PLA, effectively improving the compatibility of PLA and Pebax at the interface, which is more conducive to forming a core-shell structure.

[0040] Table 2

[0041] Proteinase K enzymatic digestion experiment: The samples of the PLA composite materials prepared in Example 10 and Comparative Example 1 were molded into films with a thickness of about 100 μm, cut into thin strips with a length and width of 20 mm×5 mm, and placed in a small centrifuge tube containing 5 mL of PBS buffer (pH=8.5). The samples were treated with proteinase K at a concentration of 0.5 mg / mL and maintained at a constant temperature in a 37°C water bath. The films were taken out regularly, washed with distilled water, and the samples were dried until the weight was stable, and the final weight was recorded. Table 3 shows the data of the residual weight change over time for Comparative Example 1 and Example 10 in a weakly alkaline proteinase K environment. It can be seen from Table 3 that the degradation rates of Comparative Example 1 and Example 10 are similar, and it can be seen that the non-biodegradable SiO 2 The impact on the biodegradability of PLA composites is minimal, which ensures the balance of rigidity and toughness of PLA composites while also ensuring biodegradability to a certain extent.

[0042] Table 3

[0043] The present invention combines biodegradable Pebax-GMA and inorganic rigid particles SiO 2 PLA composites were prepared by blending with PLA. SiO 2 The core is made of Pebax-GMA, which has excellent flexibility, wear resistance and good biodegradability, and is used as a shell. The shell is wrapped around the core to form a core-shell structure. At the same time, the present invention retains the advantage of PLA being biodegradable. On this basis, the biodegradable polymer Pebax-GMA is introduced to make the PLA composite material have excellent biodegradability, and at the same time, a material design of rigidity-toughness balance and biodegradability is achieved.

[0044] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0045] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A polylactic acid composite material with balanced rigidity and toughness, characterized in that: The invention is prepared from the following components in parts by weight: 16 parts of polylactic acid, 1-3 parts of polyetheramide copolymer grafted with glycidyl methacrylate, and 1-3 parts of silicon dioxide.

2. The polylactic acid composite material with balanced rigidity and toughness according to claim 1, characterized in that: The silicon dioxide comprises hydrophobic silicon dioxide and hydrophilic silicon dioxide, and the particle size of the silicon dioxide is 200-800 nm.

3. The polylactic acid composite material with balanced rigidity and toughness according to claim 1, characterized in that: The preparation method of the polyetheramide copolymer grafted with glycidyl methacrylate comprises the following steps: adding the polyetheramide copolymer into an internal mixer for premixing, and then adding glycidyl methacrylate, vinyl-2-pyrrolidone and dicumyl peroxide for blending to prepare the polyetheramide copolymer grafted with glycidyl methacrylate.

4. The polylactic acid composite material with balanced rigidity and toughness according to claim 3, characterized in that: The polyetheramide copolymer is prepared from polyethylene glycol and bio-based nylon 11.

5. The polylactic acid composite material with balanced rigidity and toughness according to claim 3, characterized in that: The mass ratio of the polyetheramide copolymer, glycidyl methacrylate, vinyl-2-pyrrolidone and dicumyl peroxide is 100:3-5:3-5:0.3-0.

5.

6. The polylactic acid composite material with balanced rigidity and toughness according to claim 3, characterized in that: The premixing time is 2 minutes; the blending time is 3 to 5 minutes; the blending temperature is 175 to 185° C.; and the blending speed is 40 to 80 rpm.

7. A method for preparing a polylactic acid composite material with a balanced rigidity and toughness as claimed in any one of claims 1 to 6, characterized in that: The method comprises the following steps: polylactic acid, polyetheramide copolymer grafted with glycidyl methacrylate and silicon dioxide are placed in an oven for drying; the dried polylactic acid, polyetheramide copolymer grafted with glycidyl methacrylate and silicon dioxide are weighed in proportion and put into an internal mixer for melting and blending to obtain a polylactic acid composite material.

8. The method for preparing a polylactic acid composite material with a balanced rigidity and toughness according to claim 7, characterized in that: The drying time is 12 h and the drying temperature is 50°C.

9. The method for preparing a polylactic acid composite material with a balanced rigidity and toughness according to claim 7, characterized in that: The melt blending temperature is 180° C. and the melt blending time is 5 min.

10. The method for preparing a polylactic acid composite material with balanced rigidity and toughness according to claim 7, characterized in that: The melt blending rotation speed is 80 rpm.

Citation Information

Patent Citations

  • Polylactic acid composite material and preparation method thereof

    CN103788605A

  • Method for improving mechanical properties of polylactic acid by using rigid-flexible core-shell nanoparticles

    CN109021511A

  • High-toughness biodegradable polylactic acid composite material and preparation method thereof

    CN118063943A

Cited By

  • Polybutylene succinate composite material as well as preparation method and application thereof

    CN120682614A